2005
DOI: 10.1097/01.prs.0000149479.96088.5d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic versus Static Splinting of Simple Zone V and Zone VI Extensor Tendon Repairs: A Prospective, Randomized, Controlled Study

Abstract: The authors present the first prospective, randomized, controlled study comparing postoperative dynamic versus static splinting outcomes of patients following extensor tendon repair. Patients who incurred simple and complete lacerations of their extensor tendons in zones V and VI were enrolled into the study and underwent either static splinting (n = 17) or dynamic splinting (n = 17) following primary acute repair of tendons. Total active motion was improved in the dynamic group when compared with the static g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 14 publications
3
33
0
1
Order By: Relevance
“…Early total active motion (4–6 weeks) was greater with dynamic extension orthoses (191–214°) and relative motion orthoses (205–236°) compared to static orthoses (79–202°), though three studies found that there was no difference in long-term follow-up. 9,31,32 Grip strength was not as reliably measured in all studies, but, those that did measure it, found greater improvement in the EAM patients than those treated statically (DEO 35–38 kg/89% contralateral side; RMO 85–95% contralateral side; static 23–34 kg/59% contralateral side). 911,21,30,31,34 The timing of return to work was not reported all studies, but in three studies investigating a specific EAM protocol – the immediate relative motion protocols (IRAM) using the RMO – patients returned to light duties at work around 3 weeks postoperative (3.2–3.9) compared to 9.4 weeks for static orthoses.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Early total active motion (4–6 weeks) was greater with dynamic extension orthoses (191–214°) and relative motion orthoses (205–236°) compared to static orthoses (79–202°), though three studies found that there was no difference in long-term follow-up. 9,31,32 Grip strength was not as reliably measured in all studies, but, those that did measure it, found greater improvement in the EAM patients than those treated statically (DEO 35–38 kg/89% contralateral side; RMO 85–95% contralateral side; static 23–34 kg/59% contralateral side). 911,21,30,31,34 The timing of return to work was not reported all studies, but in three studies investigating a specific EAM protocol – the immediate relative motion protocols (IRAM) using the RMO – patients returned to light duties at work around 3 weeks postoperative (3.2–3.9) compared to 9.4 weeks for static orthoses.…”
Section: Resultsmentioning
confidence: 92%
“…9,31,32 Grip strength was not as reliably measured in all studies, but, those that did measure it, found greater improvement in the EAM patients than those treated statically (DEO 35–38 kg/89% contralateral side; RMO 85–95% contralateral side; static 23–34 kg/59% contralateral side). 911,21,30,31,34 The timing of return to work was not reported all studies, but in three studies investigating a specific EAM protocol – the immediate relative motion protocols (IRAM) using the RMO – patients returned to light duties at work around 3 weeks postoperative (3.2–3.9) compared to 9.4 weeks for static orthoses. 10,33,34 Only one study 28 (of 100 subjects) experienced tendon ruptures, with one in the EAM group and 2 in the dynamic extension orthosis group.…”
Section: Resultsmentioning
confidence: 92%
“…25 They found significantly better total active motion (TAM) and grip strength in the early dynamic mobilization group at 8 weeks (p ϭ .05) but no difference at 6 months. The authors recommended early dynamic mobilization for highly motivated and compliant patients, but warned of increased risk of complications such as extensor tendon rupture and extensor lag.…”
Section: Rehabilitationmentioning
confidence: 95%
“…[19][20][21] Immobilization of the wrist and metacarpophalangeal joints Immobilization following simple zone V and VI extensor tendon repairs has been shown to produce excellent outcomes at 6 months after repair. 22 However, in complex injuries with multiple tendon involvement and/or metacarpal fractures, immobilization produces dense adhesion formation, which limits active and passive tendon glide during both digital flexion and extension. Immobilization should be reserved for noncompliant patients or children.…”
Section: Complicationsmentioning
confidence: 99%